2022
DOI: 10.3390/foods11071032
|View full text |Cite
|
Sign up to set email alerts
|

Wheat Germ and Lipid Oxidation: An Open Issue

Abstract: Wheat germ (WG)’s shelf life after the milling process is incredibly short because of the presence of enzymes that aggravate the oxidation process; thus, stabilization is required in order to exploit the nutrients and bioactive compounds within WG. The critical point for the oxidation process is the mechanical treatment used to separate WG from the kernel, which exposes the lipid fraction to the air. Showing the connection between the quality of durum wheat, considering its storage management, and wheat germ o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
2
4
0
Order By: Relevance
“…Also, the highest fatty acid was the linolic acid (50.90%). Concerning the unsaponifiable matter, for the WG oil, our results agreed with Marzocchi et al [44], who reported that WG oil contains campesterols (18.5%) and sitosterol (18.8%).…”
Section: Discussionsupporting
confidence: 92%
“…Also, the highest fatty acid was the linolic acid (50.90%). Concerning the unsaponifiable matter, for the WG oil, our results agreed with Marzocchi et al [44], who reported that WG oil contains campesterols (18.5%) and sitosterol (18.8%).…”
Section: Discussionsupporting
confidence: 92%
“…The amino acid composition of wheat germ protein is similar to that of the reference protein reported by Food and Agriculture Organization (FAO) (Boukid et al, 2018; FAO, 2007; Liao et al, 2020). Due to the high content of enzymes, for example, lipase and lipoxygenase, and the presence of unsaturated fatty acids, wheat germ is characterized by a short shelf life (Marti et al, 2014; Marzocchi et al, 2022). Currently, many physical, chemical, and biological methods are used to extend the shelf life of wheat germ (Boukid et al, 2018; Liao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Oil was extracted using a Soxhlet apparatus (Behr Labor-Technik, Fischer Scientific Italia, Milano, Italy), as reported by Marzocchi et al [ 8 ] and in accordance with the AOAC Official Method [ 9 ] (AOAC International Website). About 10 g of ground wheat fractions were placed in a cellulose thimble, and oil was extracted using a refluxing n ˗hexane.…”
Section: Methodsmentioning
confidence: 99%
“…The procedure for sterol analysis was the same as reported by Marzocchi et al [8]. After the addition of 0.5 mL of 5α-cholestan-3β-ol (c = 2 mg/mL) as the internal standard, Foods 2023, 12, 3036 4 of 12 250 mg of oil were saponified with 10 mL of 2 N methanolic potassium hydroxide at room temperature for 20 h [12].…”
Section: Sterol Analysismentioning
confidence: 99%